Patigan: Model Pemberdayaan Masyarakat dalam Pemanfaatan Aset Berbasis Kearifan Lokal - Mistarija Mistarija; Shovia Lintina; Bukhari Bukhari; Fitra Yanti (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This article discusses the patigan revenue sharing system based on the practices of the Nagari community of Sungai Nanam, Solok, West Sumatra. The goal is to explore and develop the Patigan model as a community empowerment approach based on local assets and indigenous wisdom. The Patigan model, rooted in the traditional one-third profit-sharing value of the Minangkabau agrarian culture, embodies the spirit of justice, mutual cooperation, and social trust. Employing a descriptive qualitative approach, the research was conducted in Nagari Sungai Nanam, West Sumatra, through participatory observation, in-depth interviews, and focus group discussions (FGDs). The findings reveal that local assets such as natural resources, customary social structures, religious values, and local knowledge play a vital role in the empowerment process. The Patigan process has been shown to enhance participation, strengthen social cohesion, and foster community self-reliance. This study concludes that the Patigan model holds potential as a contextual local alternative to global empowerment approaches such as Asset-Based Community Development (ABCD). It is hoped that this model can be replicated and further developed to support sustainable community-based development.